Obraz likwidacji Uniwersytetu Stefana Batorego w Wilnie w ówczesnej prasie lokalnej 3 . Część 1: Prasa polska - Franz, Maciej; Michliński, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Likwidacja Uniwersytetu Stefana Batorego w Wilnie po zajęciu miasta przez wojska sowieckie w 1939 r. miała kilka etapów. Sowieci niszczyli to, co mogli, materialnie, ale samo Wilno postanowili oddać na chwilę Litwinom. Litwa, wierząc w swoją wyjątkową pozycję, dążyła do „sprawiedliwości dziejowej”, czyli unicestwienia polskości Wilna i Wileńszczyzny. Celem szczególnie ważnym była kasacja Uniwersytetu ‒ najważniejszego polskiego ośrodka nauki i kultury tych ziem. Proces ten wywoływał spore poruszenie w mieście i miał swój oddźwięk w prasie lokalnej. Jak przedstawiała go prasa polska? Jakie kwestie były dla niej szczególnie ważne i na ile można dzięki zachowanemu materiałowi źródłowemu odtworzyć strategię niszczenia polskiej uczelni przez nowe władze litewskie? Swoimi działaniami Litwini przygotowali grunt dla Sowietów, którzy już za moment zajęli całą Litwę.

The liquidation of the Stefan Báthory University in Vilnius after its occupation by Soviet troops in 1939 was a process. The Soviets destroyed what they could materially, but they decided to give Vilnius itself to the Lithuanians for a while. Lithuania, believing in its unique position, sought "historical justice", i.e. the liquidation of the Polishness of Vilnius and the Vilnius region. A particularly important goal was the liquidation of the University; a most important Polish centre of science and culture. This process caused quite a stir in the city and was reflected in the local press. So how did the Polish press present this process? What issues were of particular importance, and to what extent it is possible, thanks to the preserved source material, to recreate the process of destruction of the Polish university by the new Lithuanian authorities. With their actions, the Lithuanians prepared the ground for the Soviets, who soon occupied the entire Lithuania.
The perception of the liquidation the Stefan Báthory University in Vilnius in the contemporary local press
Keywords: Uniwersytet Stefana Batorego; Wilno; prasa lokalna; stosunki międzynarodowe; II wojna światowa; II Rzeczpospolita; Republika Litwy; Stefan Batory University; Vilnius; local press; international relations; World War II; Second Polish Republic; Republic of Lithuania